Komunikasi Beda Gender dalam Masyarakat Bugis di Desa Kemujan Kepulauan Karimunjawa - Latief, Muhammad Chaerul (Jurnal The Messenger, 2016)
This article is the result of research on the concept of 'unggah ungguh' or how etiquette to communicate on Bugis Society influenced gender differences. This research was conducted in the Kemujan village, Karimunjawa Islands, Jepara, Central Java Province. This study used descriptive qualitative method in relation to culture. The study also used participatory observation method, is observe how communication between men with women, and at the same depth interviews with informants. The results showed that gender differences affect how to communicate the Bugis Communities in the Kemujan village. In addition, there is a tendency of the Bugis people in the village using the said call gender-biased. Nonetheless, the difference was also influenced by other aspects such as age factor, social status and situation.